2012
DOI: 10.1007/s12672-012-0105-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Estrogen Receptor Beta in Early Versus Metastatic Non-small Cell Lung Cancer

Abstract: Although women have an increased susceptibility to lung cancer, they also have a favorable clinical outcome. This may in part be due to female specific genetic and hormonal factors. In the present study, expression of ER-beta was investigated by immunohistochemistry using tissue samples from two cohorts: non-small cell lung cancer (NSCLC) diagnosed in 1999 in Manitoba and advanced NSCLC patients from the NCIC-CTG BR.18 trial. In the Manitoba cohort assessable tissue samples available in 79 patients (32 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…However, alternative studies identified that ER-β also exhibited a high expression level in male patients with lung cancer (22), that ER-β expression was higher in males compared with females (23), and that no association existed between ER-β expression and gender in patients with NSCLC (24). Thus, the presence of an association between ER-β expression and gender is inconclusive.…”
Section: Overall Survival -------------------------------------------mentioning
confidence: 99%
“…However, alternative studies identified that ER-β also exhibited a high expression level in male patients with lung cancer (22), that ER-β expression was higher in males compared with females (23), and that no association existed between ER-β expression and gender in patients with NSCLC (24). Thus, the presence of an association between ER-β expression and gender is inconclusive.…”
Section: Overall Survival -------------------------------------------mentioning
confidence: 99%
“…Conversely, cytoplasmic ERβ-1 expression was found to be a strong negative prognostic indicator for lung cancer in both males and females [40]. In a separate study, nuclear ERβ-1 also correlated with poor survival but only in the metastatic setting [53]. By contrast, other ERβ isoforms, such as ERβ-2 and ERβ-5 have been linked to better lung cancer outcome [54].…”
Section: Critical Mediators Of the Estrogen Signaling Pathway Are Expmentioning
confidence: 99%
“…The epitopes for clones H-150 and 14C8 are in the N-terminus of ER-β, and their detection rates in the nucleus are 51%-74% and 42%-71%, respectively [9,[16][17][18]27,28] . The epitope for the third clone, PPG5/10, is in the C-terminus, and the detection rate in the nucleus is 61%-84% [10,14,26,29] .…”
Section: D5mentioning
confidence: 99%
“…Omoto et al [6] NS Nucleus 67% Kawai et al [9] H-150 Nucleus 51% Schwartz et al [10] PPG5/10 Nucleus 61% Wu et al [11] NS Nucleus 46% Márquez-Garbán et al [13] Polyclonal Nucleus 52% Cytoplasm 69% Skov et al [14] PPG5/10 Nucleus 84% Niikawa et al [15] MS-ER β13-PX1 Nucleus 90% Alì et al [26] PPG5/10 Nucleus 75% Nose et al [16] H-150 Nucleus 74% Raso et al [17] H-150 Nucleus 56% Cytoplasm 98% 14C8 Nucleus 42% Cytoplasm 19% Abe et al [18] 14C8 Nucleus 71% Mauro et al [20] NS Nucleus 40% Cytoplasm 64% Navaratnam et al [27] 14C8 Nucleus 49% Rouquette et al [25] Polyclonal Nucleus 38% Karlsson et al [28] 14C8 Nucleus 86% Liu et al [29] PPG5/10 Nucleus 45% Cytoplasm 59% NS: Indicates not specified.…”
Section: Antibody Clone Location Detection Ratesmentioning
confidence: 99%